Prophylaxis of Graft-Versus-Host Disease in Unrelated Donor Transplantation With Pentostatin, Tacrolimus, and Mini-Methotrexate: A Phase I/II Controlled, Adaptively Randomized Study - Parmar, Simrit (American Society of Clinical Oncology, 2011)
PURPOSE: Acute graft-versus-host disease (aGVHD) is a major cause of morbidity and mortality after matched unrelated, related, or mismatched related donor hematopoietic stem-cell transplantation (HSCT). Improved GVHD prevention methods are needed. Pentostatin, an adenosine deaminase inhibitor, leads to lymphocyte depletion with low risk of myelosuppression. We hypothesized that addition of pentostatin to GVHD prophylaxis with tacrolimus and mini-methotrexate may improve outcomes, and we conducted a Bayesian adaptively randomized, controlled, dose-finding study, taking into account toxicity and efficacy. PATIENTS AND METHODS: Success was defined as the patient being alive, engrafted, in remission, without GVHD 100 days post-HSCT and no grade ≥ 3 GVHD at any time. Patients were randomly assigned to pentostatin doses of 0, 0.5, 1.0, 1.5, and 2.0 mg/m(2) with drug administered on HSCT days 8, 15, 22, and 30. Eligible patients were recipients of mismatched related (n = 10) or unrelated (n = 137) donor HSCT. RESULTS: Median age was 47 years. Thirty-seven, 10, 29, 61, and 10 patients were assigned to the control and four treatment groups, respectively, with comparable baseline characteristics. Pentostatin doses of 1.0 and 1.5 mg/m(2) had the highest success rates (69.0% and 70.5%) versus control (54.1%). The posterior probabilities that the success rates were greater with 1.5 mg/m(2) or 1.0 mg/m(2) versus control are 0.944 and 0.821, respectively. Hepatic aGVHD rates were 0%, 17.2%, and 11.1%, respectively, for 1.5 mg/m(2), 1.0 mg/m(2), and control groups. No grades 3 to 4 aGVHD occurred in 11 HLA-mismatched recipients in the 1.5 mg/m(2) group. CONCLUSION: Pentostatin increased the likelihood of success as defined here, and should be further investigated in larger randomized, confirmatory studies.